Hubungan Antara Narrative Engagement dan Binge Watching pada Pengguna Netflix - Nazmah Shafarani Tenia; Suci Nugraha (Bandung Conference Series: Psychology Science, 2023)
Abstract. The development of a Video on Demand streaming platform in recent years has triggered the emergence of a new phenomenon called binge watching, this phenomenon is defined as watching several episodes at once of the same TV series. One of the things that can cause someone to do binge watching is the formation of a sensation of involvement with the narrative of the spectacle (narrative engagement) both cognitively and emotionally. This research was conducted with a correlational quantitative approach to determine the relationship between narrative engagement and binge watching, especially for Netflix users, considering that the platform is the most widely used for binge watching in Indonesia. The participants in this study were 250 people aged 18-25 years and were watching TV series through the Netflix platform in Bandung City by filling out online questionnaires via google form. The measuring instrument used in this study is a measuring instrument that has been adapted by the researcher into Indonesian from the Single-Program Binge watching Scale (SPBWS) developed by Viens & Farrar (2021) and the Narrative engagement Scale developed by Bilandzic & Busselle ( 2009). The results of this study indicate a significance value of 0.000 <0.05, meaning that there is a significant positive relationship between narrative engagement and binge watching on Netflix users in Bandung with a correlation coefficient of 0.387. Abstrak. Pengembangan platform streaming Video on Demand dalam beberapa tahun terakhir telah memicu munculnya sebuah fenomena baru yang disebut sebagai binge watching, fenomena ini diartikan sebagai menonton beberapa episode secara sekaligus dari serial TV yang sama. Salah satu hal yang dapat menjadi penyebab seseorang melakukan binge watching adalah terbentuknya sensasi keterlibatan dengan narasi tontonan (narrative engagement) baik secara kognitif maupun emosional. Penelitian ini dilakukan dengan pendekatan kuantitatif korelasional untuk mengetahui hubungan narrative engagement dan binge watching khususnya pada pengguna Netflix, mengingat bahwa platform tersebut paling banyak digunakan untuk melakukan binge watching di Indonesia. Partisipan dalam penelitian ini berjumlah 250 orang yang berusia 18-25 tahun dan sedang menonton serial TV melalui platform Netflix di Kota Bandung dengan mengisi kuesioner secara online melalui google form. Alat ukur yang digunakan dalam penelitian ini adalah alat ukur yang telah diadaptasi oleh peneliti ke dalam Bahasa Indonesia dari skala Single-Program Binge watching Scale (SPBWS) yang dikembangkan oleh Viens & Farrar (2021) dan Narrative engagement Scale yang dikembangkan oleh Bilandzic & Busselle (2009). Hasil penelitian ini menunjukkan nilai signifikansi 0.000 < 0.05, artinya terdapat hubungan positif yang signifikan antara narrative engagement dan binge watching pada pengguna Netflix di Kota Bandung dengan nilai koefisien korelasi 0.387.